An experimental study on RC columns repaired on all four sides with cementitious mortars. (10th February 2018) - Ortega, A. Irene; Pellicer, Teresa M.; Adam, Jose M.; Calderón, Pedro A.
Graphical abstract: Highlights: A study was carried out on RC columns repaired with cement-based mortars. 18 specimens were tested, being subjected to compressive axial loads. The influence of the type of repair mortar (R3 and R4 Class) was studied. The presence of bonding agents between the mortar and the column was also studied. Abstract: This paper describes a study carried out in the ICITECH laboratories (Universitat Politècnica de València) on RC columns repaired on all four sides with cementitious-based mortars. A total of 18 specimens were tested, representing a group of square 20 × 20 mm 2 columns subjected to compressive axial loads. Different repair scenarios were considered in order to study the influence of the type of mortar used and the presence or absence of bonding agents between the mortar and the column concrete. The results obtained showed that bonding agents have no appreciable effect on the behaviour of the repaired columns. Of the two types of mortar used in the study (Classes R3 and R4), the columns repaired with the lower grade mortar (R3) were seen to behave better. The main novelty of this work lies in the fact that this is the first time that two types of mortar are compared in the repair of four column sides, in addition to the possible use of bonding agents between the mortar and the column.